2018
DOI: 10.1513/annalsats.201802-112oc
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Breathing Measurements at Discharge and Clinical Outcomes in Extremely Low Gestational Age Neonates

Abstract: Extremely premature infants receiving less than 1 L/min nasal cannula support at 21% to 100% fraction of inspired oxygen have tidal breathing measurements that differ from term infants, but these measurements do not differentiate those preterm infants who have BPD or will have respiratory disease in the first year of life from those who do not. Clinical trial registered with www.clinicaltrials.gov (NCT01435187).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…We initially anticipated that TVs and minute ventilation would remain the same or be decreased with increasing severity of BPD, with the traditional physiological assumption that hyperinflation and gas trapping would increase tachypnea and diminish efficient ventilatory mechanics. However, recent studies have observed that abnormal tidal breathing patterns in extremely preterm infants, which may or may not be related to severity of BPD . It has been suspected that increased chest wall compliance in neonates causes them to have a reduced FRC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We initially anticipated that TVs and minute ventilation would remain the same or be decreased with increasing severity of BPD, with the traditional physiological assumption that hyperinflation and gas trapping would increase tachypnea and diminish efficient ventilatory mechanics. However, recent studies have observed that abnormal tidal breathing patterns in extremely preterm infants, which may or may not be related to severity of BPD . It has been suspected that increased chest wall compliance in neonates causes them to have a reduced FRC .…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have observed that abnormal tidal breathing patterns in extremely preterm infants, which may or may not be related to severity of BPD. 35 It has been suspected that increased chest wall compliance in neonates causes them to have a reduced FRC. 22 Central respiratory receptors would normally cause infants to begin inspiration before complete expiration in an effort to maintain gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…coughing, wheezing, respiratory infections, respiratory drug use) have been reported in survivors of preterm birth [4,5]. Lung function in survivors of extreme preterm birth is significantly different from term controls at long term, even in the absence of BPD or oxygen dependency [6,7]. Most importantly, a model based on perinatal characteristics such as gestational age, birth weight, sex, race, familial history and intubation at birth is a better predictor for respiratory outcomes than the presence of BPD (as defined by the need for supplementary oxygen) [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence of persistent pulmonary morbidity in BPD survivors even in the post-surfactant era (2,88,89). However, BPD diagnosis does not necessarily predict long-term lung function (89)(90)(91). Vice versa, a high incidence of respiratory morbidity has been described in children born preterm, even in the absence of BPD (89,90).…”
Section: Association Of Niv With Outcome Measures Other Than Bpd and mentioning
confidence: 99%